Peran Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Terhadap Perlindungan Hukum Anak Korban Eksploitasi Ekonomi Di Lampung - Yulia Hesti; Adelia Amanda Hidayat; Liza Indah Purnama (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
The city of Bandar Lampung is one of several cities in Lampung Province with relatively high rates of exploitation of children. One form of exploitation is economic exploitation. This research aims to analyze the effectiveness of the roles and duties of the PPPA Bandar Lampung City office. This research uses normative and empirical juridical research methods. The problems discussed in this research are what causes children to become victims of economic exploitation and what is the role of the Women's Empowerment and Child Protection Service (PPPA) in the legal protection of children as victims of economic exploitation. The results of the research show that the biggest factor causing children to experience economic exploitation is economic factors, so this requires special attention from the government, regional government and the women's empowerment and child protection (PPPA) service in reducing poverty rates and helping children obtain their rights by how to provide socialization and assistance to children as victims of economic exploitation practices.